Pengaruh Citra Merek, Harga, Kualitas Pelayanan terhadap Keputusan Pembelian Springbed pada Distributor PT. Duta Abadi Primantara - Hana Pertiwi, Danik; Simatupang, Lucy Nancy (Jurnal Manajemen, 2024)
This research intends to understand the influence of Brand Image, Price and Service Quality on Springbed Purchasing Decisions at PT. Primantara Eternal Ambassador. The evidence used is primary evidence collected through gathering sources from 50 sources who have purchased spring beds at the distributor PT. Primantara Eternal Ambassador. The process in this research is Causal Design. The process used in this research is a quantitative method and the research effect is based on respondents' answers using the LikeArt scale method. The data analysis techniques used in this research describe the Normality Test, Multiple Linear Regression Test, F Test, t Test and Coefficient of Determination with the help of SPSS 23. The results of the observations state that simultaneously (F Test) a significant influence is received between the Brand Image variables (X1 ), Price (X2), and Service Quality (X3) on Purchasing Decisions (Y). Partially (t test) Brand Image (X1) received a significant influence on Purchasing Decisions, Price (X2) received a significant influence on Purchasing Decisions and Service Quality (X3) received a significant influence on Purchasing Decisions.